Dampak Beasiswa Tahfidz bagi Penerus Bangsa yang Berakhlak - Muhammad Yusron Maulana El-Yunusi; Didit Darmawan; Wulandari; Mirza Elmy Safira; Laila Badriyah; Roidatus Shofiyah; Siti Kholidatur Rodiyah; Masfufah; Rahayu Mardikaningsih; Nailul Ulah Al Chumairoh Machfud; Uswatun Chasanah; Amir Bandar Abdul Majid (Forum Kerjasama Pendidikan Tinggi, 2024)
Scholarships have a role in improving the quality of a nation's human resources, but the benefits are still not felt equally in Indonesia. The main obstacle is the limited information about scholarships. To overcome this challenge, scholarship counseling activities need to be held regularly to convey information to the community. Sunan Giri University Surabaya initiated tahfidz scholarship counseling as an effort to provide understanding to the community. The main purpose of this counseling is to provide information about tahfidz scholarships offered by Sunan Giri University Surabaya. In addition, this activity provided an opportunity for counseling participants, who this time came from 60 students of MA Salafiyah Syafi'iyah Seblak Jombang, to ask questions directly to the speakers about the scholarship registration process. In this way, participants were able to understand in detail the intricacies of the tahfidz scholarship program. The tahfidz scholarship counseling organized by Sunan Giri University Surabaya was not only informative but also useful. Participants not only gained knowledge about the requirements and benefits of the tahfidz scholarship, but were also inspired to take a step by applying for the scholarship. Through this activity, it is hoped that counseling participants can become information ambassadors in their environment and invite more individuals to take advantage of tahfidz scholarship opportunities. Thus, the tahfidz scholarship outreach is not only a source of information, but also an effective motivational tool to increase community participation in achieving educational opportunities. With this activity, the benefits of the tahfidz scholarship can be felt more evenly in the community, bringing a positive impact on the development of the quality of human resources and education in Indonesia.